Feeling Unsafe Among Female Users of Crowded Public Transportation - Ismawati, Ismawati; Saut H. Hutahaean, Erik; Fahrudin, Adi (Rifa'Institute, 2023)
Introduction: Sexual harassment is a serious problem; it often occurs in public spaces, especially on crowded public transportation. In acts of sexual harassment, women are considered more vulnerable to being victims. The impact of these acts of sexual harassment is the emergence of insecurity among female users; Feeling of security is considered the most important factor when one uses public transportation. Objective: This study analyzes the importance of the insecurity women feel when using congested public transportation. Method: A total of 215 female respondents using dense public transportation were involved in filling out the insecurity scale research questionnaire, the Personal Safety Perception Index. The collected data is then analyzed using correlation and regression statistical techniques. Result and Discussion: The results of the study stated that the insecurity felt by women when using crowded public transportation can influence fear of crime, especially in sexual harassment crimes. Conclusion: It can be concluded that insecurity in women who use public transportation is very influential on the condition both psychologically and physically of the woman